Attributes Related to Collectivism in Japanese Industrial Organizations in Hungary - Balogh, Mónika (Journal of East Asian Cultures, 2022)
The present article develops a view of attributes related to collectivism in Japanese industrial organizations (companies) located in Hungary, on the basis of fieldwork. After a short overview of research in the field of individualism and collectivism, several arguments and also incidents are presented which reveal the collectivistic nature of the examined social sample. The evaluation and analysis of the related phenomena will be conducted based on sociological concepts such as kojinshugi, 個人主義, dantaishugi, 団体主義, kosei, 個性, uchi, 内, soto, 外 and others. Both the concepts and the terminology used in monocultural and cross-cultural studies are examined, before being compared and differentiated from each other.